Assessment of human leukocyte antigen immunogenicity: current methods, challenges and opportunities. Issue 4 (August 2018) - Copley, Hannah C.; Elango, Madhivanan; Kosmoliaptsis, Vasilis
Abstract : Purpose of review: Donor–recipient human leukocyte antigen (HLA) matching improves outcomes after solid-organ transplantation, but current assessment of HLA incompatibility is inadequate as it does not consider the relative immunogenicity of individual HLA mismatches. In this article, we review existing strategies for assessing HLA immunogenicity and discuss current challenges and future opportunities in this field. Recent findings: Current HLA immunogenicity algorithms focus primarily on the humoral component of the alloimmune response and aim to determine a measure of 'dissimilarity' between donor and recipient HLA. This can be achieved by deriving information from comparison of donor and recipient HLA at the amino acid sequence, structural and/or the physicochemical level, accounting for both B-cell and T-cell pathways of alloreactivity. Substantial evidence now supports the superiority of this molecular definition of HLA incompatibility, over conventional enumeration of HLA antigenic differences, for assessing the risk of humoral alloimmunity and for predicting graft outcomes after transplantation. Summary: Significant progress has been made in developing computational HLA immunogenicity algorithms that offer exciting opportunities for a more rational approach to determining the degree of donor–recipient HLA incompatibility and to defining HLA-related immunological risk. A number of challenges now need to be overcome to enable their implementation into clinical practice.